Control of a variable speed asynchronous wind turbine dedicated to isolated site - Taoufik Ouchbel; Smail Zouggar; M. L. Elhafyani; Mohammed Mokhtari; Mohamed Oukili; Fatima Zahra Kadda (Institute of Advanced Engineering and Science, 2020)
This paper focuses on the study of the asynchronous generator self-excited during operation in isolated mode. It concerns the analysis of a robust control of the asynchronous machine in order to improve the quality of the electrical energy produced in different environmental circumstances, and to promote the use of renewable energies in rural areas to improve education, the supply of drinking water, livestock and agriculture, access to information and communication. The present work concerns the description and modeling of the various mechanical parts of the wind turbine. It also tackles the steady-state and transient modeling of the asynchronous generator under self-excitation conditions. The practical results and the simulation ones have shown the influence of the self-excitation capacity on the output quantities of the wind system (voltage, current and torque) in vacuum and under charge (resistive and inductive). In the case where the asynchronous wind turbine is connected to a network, it imposes amplitude, waveform and frequency. But in the case of isolated sites, the asynchronous machine has a low power factor, what means it requires reactive energy. To correct this irregularity, we can improve the power factor by using variable capacitors. The excitation current (reactive power) must be permanently supplied according to the load connected. This requires an intelligent system that regulates the electrical energy produced.